2011
DOI: 10.1140/epjst/e2011-01374-6
|View full text |Cite
|
Sign up to set email alerts
|

Receding contact lines: From sliding drops to immersion lithography

Abstract: Abstract. Instabilities of receding contact lines often occur through the formation of a corner with a very sharp tip. These dewetting structures also appear in the technology of Immersion Lithography, where water is put between the lens and the silicon wafer to increase the optical resolution. In this paper we aim to compare corners appearing in Immersion Lithography to those at the tail of gravity driven-drops sliding down an incline. We use high speed recordings to measure the dynamic contact angle and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 23 publications
4
72
0
Order By: Relevance
“…3, a smaller value of h r would be expected, contrary to the experimental results. Winkels 44 measured the shape of isothermal sliding droplets as a function of speed and found that the opening angle at the critical substrate speed equalled u ¼ 60…”
Section: Discussionmentioning
confidence: 99%
“…3, a smaller value of h r would be expected, contrary to the experimental results. Winkels 44 measured the shape of isothermal sliding droplets as a function of speed and found that the opening angle at the critical substrate speed equalled u ¼ 60…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that, when the substrate is moving too fast, droplets are emitted at the receding part of the liquid similar to what happens in the moving drop case, see Fig. 1.2b [4]. Similarly, at much higher speed, air bubbles are observed in the advancing part, suggesting entrainment of air at the advancing contact line.…”
Section: Moving Contact Linesmentioning
confidence: 83%
“…An additional complexity is that the contact line can spontaneously develop sharp corner structures, or even zig-zags. This has been observed in dip-coating [2], splashing [39], immersion lithography [4,40] and for drops sliding down an inclined plane [1,41]. The conical structure of the interface near the contact line renders the problem truly three-dimensional, which affects the balance of the capillary forces [42].…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations